PENGETAHUAN AL-QURAN DAN HADIS MELACAK KERANGKA DASAR INTEGRASI TEOLOGI DAN AGAMA - Komarudin, Didin (Al-Bayan: Jurnal Studi Al-Quran dan Tafsir, 2018)
This essay is aim at tracing the root of scientific philosophy in Islamic perspective, without overlook at the concept of the knowledge of philosophy before it is molded as the branch of philosophy. The objective is finding out the basic framework for the integration of science and Islamic knowledge. It is based on two reasons: first, based on the thesis that says that there is no dichotomous thinking in knowledge. Second, Al-Qurâan as the revelation of God is mostly considered as the source of the knowledge. Basically, the concept of knowledge in Islam is comprehensively-deeply considered, even more comprehensive than the concept of knowledge in western point of view. Thus, it is no exaggeration to say that if the contemporary science is compared with the concept of knowledge in Islam, the contemporary knowledge will be in a lower level than knowledge in Islamic concept as it is considered by modern civilization. In short, the development of knowledge in tauhid1 framework is a sine qua non to transform Moslems to be the clever and wise people. Tauhid can transform Muslims to be a person who are able to give an original, exclusive and Islamic contribution to the exiting body of knowledge, who are able to offer a solution of the humanity problem for the sake of the creation of the life that is more humane. It is also including Muslims who are able to be intellectual leadership and, at the same time be solid foundations of the construction of culture and Islamic civilization.